DISSOLUTION ENHANCEMENT OF TETRAHYDROCURCUMIN USING OPTIMIZED SELF-NANOEMULSIFYING DRUG DELIVERY SYSTEM - ASTUTI, IKA YUNI; SULIATIN, TRI; WAHYUNINGRUM, RETNO (International Journal of Applied Pharmaceutics, 2019)
Objective: The objective of this study was to optimize and enhance the dissolution of tetrahydrocurcumin (THC) using optimized self-nanoemulsifying drug delivery system (SNEDDS). Methods: The optimization was carried out with the D-optimal design using software design expert 7.15. The independent variables were the amount of oil, surfactant, and cosurfactant. The dependent variables were the emulsification time, percentage transmittance, and dissolution efficiency at minute 15 (DE15). The dissolution profile of the THC in optimum formulation compared with the unmodified THC. Results: The optimum formulation of SNEDDS consists of 10% Labrafil, 80% Kolliphor:Labrasol (1:3), and 10% PEG 400. The DE15 was 49.45%, significantly higher than the THC unmodified (p<0.05). The estimated responses were not significantly different from the experimental responses. The droplet size of the optimum formula was 53.8 nm, the polydispersity index was 0.043 and the zeta value was -19.4 mV. Conclusion: The D-optimal design was successfully determining the optimum formula of THC loaded SNEDDS. The SNEDDS formulation was increased the dissolution of THC.